The spatial–temporal evolution of Neotethyan subduction in central to Southeast Iran: Constraints from geochemistry, zircon U–Pb–Hf, and Sr–Nd–Pb isotopes - Babazadeh, Shahrouz; Raeisi, Davood; Santosh, M.; Furman, Tanya; Choi, Sung Hi; D'Antonio, Massimo (Chemical geology, 2024)
Igneous rocks in central Iran preserve proof of several episodes of Late Mesozoic–Cenozoic Neotethyan subduction, and record temporal and spatial variations from subduction to collisional geodynamic regimes that remain a subject of debate. We revisit magmatic rocks from the central Urumieh–Dokhtar magmatic arc (UDMA; 32° 30′ N to 36° 00′ N) and report new major and trace element analyses, whole-rock Sr–Nd–Pb-isotopic data and zircon U–Pb–Hf ages on plutonic rocks from the Kajan region. The data reveal magmatic pulses between 32 and 22 Ma that are represented by igneous rocks with geochemical and isotopic features resulting from melting of a metasomatized, enriched mantle. Modeling indicates the samples represent a mixture of 97% batch melt (from a source with 98.5% mantle melt +1.5% terrigenous sediment) with 3% upper continental crust. The oldest yielded age (i.e., 32 Ma) rules out a lull in magmatism in the central UDMA between 37 and 26 Ma and speaks against distinct flare-up magmatic episodes at ∼54–37 Ma and ∼ 20–5 Ma in the frontal arc. We hypothesize that magmatism records down-going slab tearing into two pieces beneath the central to SE UDMA, which then changes the geometry and buoyancy of subducting Neotethyan lithosphere. The down-going slab remained involved in central UDMA (i.e., rollback) during Early Miocene whilst arc retreat beneath the SE UDMA proceeded with detachment of subducted oceanic lithosphere (i.e., break-off). We hypothesize a diachronous collision in the UDMA, first in the southeastern segments, and subsequently in the central UDMA. These findings bear important implications for the geodynamic evolution of the Zagros orogen and run counter to a model suggesting that the collision initiated in the northwest to central and propagated progressively to the southeast along the Zagros suture zone.